RISET DAN APLIKASI SISTEM DESAIN DYNAMIC EFFECT FILM DAN TELEVISI BERBASIS ARTIFICIAL INTELLIGENCE - Chitra Lestari, S.I.Kom, M.I.Kom, Chitra Lestari, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2023)
In the process of film from visual art to audio-visual art, sound design technology provides unlimited possibilities for its development. Before the emergence of audio film, we can only understand the connotation of the film through the actor's actions and some subtitles. Until the emergence of audio film, we can not only deeply under-stand the author's ideas through the actor's lines, the rendering and contrast of sound and music, but also let it better shape its own artistic works. The same is true of television, which appeared later than movies. The design of music, sound and language plays a very important role from the early sound design to the later sound image shaping and the second creation of the sound of the whole film. Therefore, this paper studies the film and televi-sion sound dynamic effect designsystem based on artificial intelligence.